RF modulated thermionic electron gun - Mytrochenko, V.V.; Zhyglo, V.F.; Kushnir, V.A. (Problems of Atomic Science and Technology, 2022)
We present design and simulation results on the electron source for S-band technological electron linac. This device is a combination of an RF gun and a DC diode gun. The gun consists of a thermionic cathode, which is mounted on the wall of the TM₀₁₀ cavity that is under negative high voltage potential relatively to an anode. The particles dynamics has been studied by simulation. At an average particle energy of 95 keV, the beam pulse current is 0.44 A, the emittance does not exceed 4.8 mm·mrad, and 70% of all electrons are concentrated in the 72° phase range.